Humans Are More Influential Than Coyotes on Mammalian Mesopredator Spatiotemporal Activity Across an Urban Gradient - Moura, Chad W.; Clucas, Barbara; Furnas, Brett J. (Frontiers in Ecology and Evolution, 2022)
For mammalian mesopredators, human-dominated landscapes offer a mosaic of risk and reward. While the reward of anthropogenic food resources may attract mesopredators to human-dominated areas, increased mesopredator activity and abundance in these areas may cause interspecific conflict. For smaller-bodied mesopredators, the perceived risk of intraguild predation by larger mesopredators may be enough to drive spatial and temporal avoidance strategies to reduce risk while still benefiting from anthropogenic resources. We evaluated how the spatiotemporal activity of four non-canid mammalian mesopredators – raccoon (Procyon lotor), striped skunk (Mephitis mephitis), opossum (Didelphis virginiana), and domestic cat (Felis catus) – might change in the presence of an intraguild predator, the coyote (Canis latrans), and a “super predator,” humans. We quantified mesopredator activity by deploying camera traps at 110 sites across an urban gradient in the Sacramento Metropolitan Area in central California, USA. We hypothesized that mesopredators would likely change their spatiotemporal activity in response to urban intensity (H1), coyotes (H2), human presence (H3), and if urban intensity might mediate the response to humans and coyotes (H4). We used single-species occupancy models to test how mesopredators responded to different spatial scales of urbanization, as well as the temporal presence of coyotes and humans. Top single-species models then informed two-species conditional occupancy models to evaluate how mesopredators responded to “dominant” coyotes. Finally, we used temporal overlap analyzes to evaluate whether activity patterns of mesopredators changed in response to humans and coyotes across three levels of urban intensity. Mesopredators did not change their spatial or temporal activity across the urban gradient when coyotes were present. Additionally, coyotes did not influence mesopredator temporal activity at 1-3-day scales; however, raccoons and cats may avoid coyotes at finer scales. Humans influenced mesopredator detectability, as cats and coyotes avoided humans after one and two days respectively, and opossums avoided urban areas when humans were present within three days. Coyotes may play a limited role in altering smaller-bodied mesopredator activity, especially when humans are present. While the impacts of human presence and urban features are often linked, mesopredators may perceive the risk each poses differently, and adjust their activity accordingly.